2018
DOI: 10.1111/jmwh.12923
|View full text |Cite
|
Sign up to set email alerts
|

Is Sexting Associated with Sexual Behaviors During Adolescence? A Systematic Literature Review and Meta‐Analysis

Abstract: Introduction: A growing body of research has addressed adolescent use of mobile devices to exchange sexually explicit images and messages (sexting). While there are legal consequences in some states for sexting among adolescents, research findings have also demonstrated associations between sexting and sexual activity. The purpose of this systematic review was to synthesize research examining the association between adolescent sexting and sexual activity. Methods: Five databases (The Cumulative Index to Nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 36 publications
2
43
0
2
Order By: Relevance
“…Criterion validity was supported by relations between A-SextS and different variables in the available literature. This was the case for age, sexual activity, and pornography consumption, which have consistently been found to positively correlate with sexting [2,18,19]. Nine different subscales of A-SextS were also defined according to sexting action and addressees: sending sexts to a boy/girlfriend (SF), sending sexts to someone known in person (SK), sending sexts to someone known only on internet (SI), posting or live-streaming pictographic content (PS), asking for sexts from a boy/girlfriend (AF), asking for sexts from someone known in person (AK), asking for sexts from someone only known on the internet (AI), receiving sexts (R), and refusing to send sexts (RS).…”
Section: Stage 2: Concurrent and Criterion Validitymentioning
confidence: 72%
See 1 more Smart Citation
“…Criterion validity was supported by relations between A-SextS and different variables in the available literature. This was the case for age, sexual activity, and pornography consumption, which have consistently been found to positively correlate with sexting [2,18,19]. Nine different subscales of A-SextS were also defined according to sexting action and addressees: sending sexts to a boy/girlfriend (SF), sending sexts to someone known in person (SK), sending sexts to someone known only on internet (SI), posting or live-streaming pictographic content (PS), asking for sexts from a boy/girlfriend (AF), asking for sexts from someone known in person (AK), asking for sexts from someone only known on the internet (AI), receiving sexts (R), and refusing to send sexts (RS).…”
Section: Stage 2: Concurrent and Criterion Validitymentioning
confidence: 72%
“…In an ongoing meta-analysis it has also been observed that such rates have been progressively increasing over the last ten years (e.g., 7%, 95% CI: 5%, 10% for sending sexts in studies collecting data in 2009, versus 16%, 95% CI: 13%, 20% in 2014, and 29%, 95% CI: 20%, 39% in 2018) [17]. The most supported findings concerning correlates have suggested that sexting is more prevalent with increasing age [2], and is significantly related to adolescent sexual behavior, such as having actual sexual intercourse, and to other online and offline sexual experiences, such as pornography consumption [18,19]. The disparate findings in sexting research may be due to differences in how the practice has been conceptualized and measured among the various studies [2,3,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Self-esteem, an important determinant of adolescent mental health and development, has not been included in the past systematic reviews of literature and meta-analyses. Only a few studies have examined its association to sexting [1,35,36,55].…”
Section: Disclaimermentioning
confidence: 99%
“…9676 adolescents suggested that the odds of reporting sexual activity were 6.3 times higher for adolescents who sent sexts versus those who did not(Handschuh, La Cross & Smaldone, 2019).Los Angeles middle school students (N= 1285) whose excessive sexting was associated with unprotected sex (OR=12.1)(Rice et al, 2014). In a sample of Hispanic adolescents 13-21 years old, "ever sexters" had greater odds of penetrative sex (oral, vaginal and anal) as well as hormonal contraception(Romo, Garnett, Younger, Stockwell, Soren, et al, 2017).…”
mentioning
confidence: 99%